Metode Pengajaran Variatif dalam Pembelajaran Seni Tari sebagai Upaya Meningkatkan Keaktifan Siswa di SMA Negeri 10 Kaur (Pentagon) - Febriyentika, Rensi; Astuti , Fuji; Nerosti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Dance education at the senior high school level plays a strategic role in fostering students’ creativity, self-expression, and aesthetic sensitivity. However, in practice, dance learning often encounters challenges related to low levels of student activeness, both in participating in learning activities and in expressing dance movements. This article aims to describe the implementation of varied teaching methods in dance learning as an effort to enhance student activeness at SMA Negeri 10 Kaur (Pentagon). This study employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. The findings indicate that the application of varied teaching methods such as demonstration, drill exercises, discussion, group work, and the use of audiovisual media had a positive impact on increasing student activeness. Students demonstrated higher enthusiasm, greater confidence in participating, and more active engagement throughout the learning process. Therefore, varied teaching methods can be considered an effective instructional strategy for improving student activeness in dance education.